Public Sector Development Strategy as a Driver of Economic Growth: An Endogenous Growth Theory Perspective - Syamsu Rijal; Muhammad Ishlah Idrus; Muhammad Ihsan Said Ahmad (Student Research Journal, 2023)
Sustainable and stable economic growth is a key goal for many countries. As times change and global challenges become more complex, it is important for countries to develop effective strategies to promote economic growth. One sector that has an important role in this regard is the public sector. This research aims to analyse the public sector development strategy as a driver of economic growth. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the public sector development strategy as a driver of economic growth plays an important role in creating a conducive environment for sustainable and inclusive economic growth. In the context of endogenous growth theory, the government has the ability to influence the determinants of economic growth through appropriate policies and actions.